Using Meglumine Diatrizoate to improve the accuracy of diagnosis of cracked teeth on Cone‐beam CT images. (17th February 2020) - Yuan, M.; Gao, A. T.; Wang, T. M.; Liang, J. H.; Aihemati, G. B.; Cao, Y.; Xie, X.; Miao, L. Y.; Lin, Z. T.
Abstract: Aim: To explore in a laboratory setting the feasibility of using Meglumine Diatrizoate (MD) to improve the accuracy of diagnosis of cracked teeth on cone‐beam CT (CBCT) images. Methodology: Twenty‐four teeth were cracked artificially by soaking them cyclically in liquid nitrogen and hot water. The number and position of crack lines were evaluated with a dental operating microscope and used as the gold standard. The artificially cracked teeth were then examined using routine scanning (RS) and enhanced scanning (ES) modes, respectively. For the ES mode, MD was painted on the surface of the crack lines, and then, CBCT scanning with the same parameters was performed after 10 min. A radiological graduate student and an experienced radiologist evaluated the presence or absence of crack lines, respectively. The differences between the RS and ES modes were determined and assessed using McNemar's test. Inter‐examiner agreement and intra‐examiner agreement were assessed using kappa analysis. Results: Fifty‐seven crack lines were found in the 24 cracked teeth. In the RS mode, the accuracy of detection of crack lines was 23% (radiological graduate student) and 32% (experienced radiologist), whereas in the ES mode, the accuracy was 61% (radiological graduate student) and 65% (experienced radiologist). The inter‐examiner agreement was 0.693 in RS mode and 0.849 in ES mode. The intra‐examiner agreement was 0.872 and 0.949 for the radiological graduate student in RS and ES mode respectively; and one for the experienced radiologist both in RS and ES mode. Conclusions: Compared with routine scanning mode, more crack lines could be detected in enhanced scanning mode using Meglumine Diatrizoate as a contrast medium. MD could be a potential contrast medium to improve the accuracy of detection of crack lines on CBCT images.